FUNDAMENTALS OF SPIRITUALITY AND ENLIGHTENMENT USE OF ADVANCED PEDAGOGICAL TECHNOLOGIES AND INTERACTIVE METHODS IN LESSONS (World Bulletin of Public Health, 2023)
One of the important requirements for the organization of modern education is to achieve high results in a short period of time without spending too much mental and physical effort. , as well as controlling the activities of the students, assessing the level of knowledge, skills, and qualifications acquired by them, requires a high pedagogical skill from the teacher and a new approach to the educational process. Pedagogical technology is inherently subjective, that is, every teacher should creatively organize the process of education and training based on his own capabilities and professional skills. Correctly used methods deepen the knowledge of objective reality and increase the overall and scientific-theoretical level of training. Successively selected teaching methods lead to a certain level of knowledge and professional interest development, activation of independent practical activity
Keywords: Brainstorming; Snow pile; Charkhpalak